Failure of adhesive or cohesive within oil palm veneer plywood bonded with selected resin / Nur Zakiah Mohd Yasin - Mohd Yasin, Nur Zakiah (Faculty of Applied Sciences, 2016)
This study investigated the bond formation of adhesive on to the plywood form oil palm trunk (OPT) veneer. Adhesive used for the study were Urea Formaldehyde (UF), Phenol Formaldehyde (PF) and Polyvinyl Acetate (PVAc). The adhesive spread value was determined through the thickness of veneer. For bending strength the modulus of elasticity (MOE) and modulus of rupture (MOR) are significant at PSO.05. PF resins have the highest MOE and MOR at 1881.17 MPa and 12.26 MPa respectively. The tensile shear shows strength UF>PF>PVAc. The result is highly significant at PSO.01 and UF (0.51 MPa) passed the standard JAS 2014 requirement. Lastly wood failure shows a highly significant difference at PSO.01, indication that covalent bonding and cohesive failure of PF and UF is stronger than PVAc (dipolar). The highest wood failure was PF with 78%.